Changes in practices of organic certified cocoa farmers in Southwest Paraense, Eastern Amazonia (Research, Society and Development, 2019)
The production of certified organic cocoa requires significant changes in the productive and commercial practices of family farmers. This work aims to study the changes in the practices of certified organic cocoa production families in the municipalities of Pacajá, Brasil Novo and Medicilândia. Forty-seven farmers from three cooperatives of organic products were interviewed. It was identified what has influenced the changes of the productive practices of family farmers in relation to the production of cocoa beans in the region, highlighting four logics that drove such changes: a) emphasis on product quality, b) quality linked to the guarantee (c) irregularity in practices for the production of good quality almonds, and d) little influence by market encouragement. The differences between the logics are associated to the type of production of the almond, with quality (Acoaq) and conventional (ACC) and the way each farmer has adopted the changes in their systems. The changes of the systems resulting from the adopted practices and the commercialization follows more the perspective of the organic agriculture, and it was verified that some systems are few influenced by the external logics after the entry in the cooperatives. The main reasons are the lack of manpower and working capital in the cooperatives for immediate payment.